Stimulation‐Induced Dyskinesia After Subthalamic Nucleus Deep Brain Stimulation in Patients With Meige Syndrome. Issue 2 (22nd September 2020) - Wang, Ning; Wang, Kailiang; Wang, Qiao; Fan, Shiying; Fu, Zonghui; Zhang, Feng; Wang, Lin; Meng, Fangang
Abstract: Objectives: Deep brain stimulation of the subthalamic nucleus (STN‐DBS) is increasingly used to treat Meige syndrome (MS) and markedly improves symptoms. Stimulation‐induced dyskinesia (SID), which adversely affects surgical outcomes and patient satisfaction, may, however, occur in some patients. This study attempts to explore possible causes of SID. Materials and Methods: Retrospectively collected clinical data on 32 patients who underwent STN‐DBS between October 2016 and April 2019 were analyzed. Clinical outcomes were assessed pre‐ and post‐surgery, using the Burke–Fahn–Marsden dystonia rating scale (BFMDRS). Patients were divided into a dyskinesia group and a non‐dyskinesia group, according to whether or not they experienced persistent SID during follow‐up. The coordinates of the active contacts were calculated from post‐operative computerized tomography or magnetic resonance imaging, using the inter‐commissural line as a reference. At final follow‐up, the main stimulatory parameters for further study included pulse width, voltage, and frequency. Results: At final follow‐up (mean = 16.3 ± 7.2 months), MS patients had improved BFMDRS total scores compared with pre‐surgical scores (mean improvement = 79.0%, p  < 0.0001). The mean improvement in BFMDRS total scores in the dyskinesia ( n = 10) and non‐dyskinesia ( n = 22) groups were 81.6 ± 8.8% and 77.9 ± 14.2%, respectively. The mean minimum voltage to induce dyskinesia was 1.7 ± 0.3 V. The programmed parameters of both groups were similar. When compared with the non‐dyskinesia group, active stimulatory contact coordinates in the dyskinesia group were inferior (mean left side: z = −2.3 ± 1.7 mm vs. z = −1.2 ± 1.5 mm; p = 0.0282; mean right side: z = −2.7 ± 1.9 mm vs. z = −2.3 ± 1.7 mm; p = 0.0256). The x and y coordinates were similar. Conclusion: STN‐DBS is an effective intervention for MS, providing marked improvements in clinical symptoms; SID may, however occur in the subsequent programming control process. Comparing patients with/without dyskinesia, the active contacts were located closer to the inferior part of the STN in patients with dyskinesia, which may provide an explanation for the dyskinesia.